Impact of Increase in Input And Output Prices Toward Rice Production In Banten Province-Indonesia - Siagian, Viktor - (Advances in Social Sciences Research Journal, 2019)
In year 2014 the production of rice in Banten amounted to 2,045,883 tons with a harvested area of ​​386,398 ha. The objective of this study are: 1) to know the factors of influencing rice production in Banten Province, 2) to know the impact of price increase of input and output on paddy production in Banten Province. This method of study used survey method with 120 respondents. The analysis method uses Simultaneous Equations Model which was estimated using Two Stages Least Squares (2SLS) method. The results of the study were 1) The factors that affect rice production in Banten Province significantly are: Total Use of Certified Seeds, Total Use of SP-36 Fertilizers, Total Use of Solid Growing Substances, Total Use of Solid Pesticides, Total Use of Liquid Herbicides, Total Use of Labor Rent, Land area, and Farm Household Income per year. 2) From the simulation results that the increase in grain prices by 20% will increase production by 4.4% and household income of 11.6%. A 20% increase in the price of Urea and NPK fertilizers could increase rice production by 2.5% and farm household income by 1.1%. So the increase of farm input prices (fertilizer and wage of tractor and labor rent) by 20% does not affect rice production and farmer’s income. Keywords: simultaneous equation model, input and output prices, rice production.